The Jurassic Park and Ata Modo in Eastern Indonesia : A Case in Komodo National Park (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
Famous for its distinctive Komodo dragons (Varanus Komodoensis) and features home to underwater ecosystems, the Komodo National Park (KNP) has become a prominent and favorite destination of visitors locally and globally in recent years. Situated in Labuan Bajo, East Nusa Tenggara Province, Indonesia, KNP has three prime islands: Rinca, Komodo, and Padar. The infrastructure development in KNP formulated in 2020 by the central government of Indonesia, including establishing offices, photograph areas, clinics, warehouses, public spaces, and tour guides' offices, raises controversy about this decision. While the government of Indonesia persuaded citizens that this erection was a conservation effort for protection, preservation, and utilization, UNESCO refused this plan by enacting a refusal document and assessing whether the development could affect the property's Outstanding Universal Value (OUV) before the review of the relevant environmental impact analysis by the International Union for Conservation of Nature (IUCN). Additionally, the local people argue this plan will threaten the giant lizard's habitat regarding the entry of heavy equipment and disadvantage local tourism actors.Using a systematic literature review method, this piece collects and discovers a different concept in the issue of infrastructure development in KNP instead of another scholar's perspective. Walpole and Goodwin (2000) find that economics and facilities are the prominent aspects of tourism, while UNESCO considers the environment in development.In contrast to popular belief, this paper indicates a significant role of local people, known as Ata Modo, in the KNP establishment. This paper's findings propose that Ata Modo, as local people/tribes in KNP, should not be relocated from their area and instead be involved in the decision-making process. The bottom-up approach can be executed as a practice in a democratic process. From the fiscal approach, this development will positively impact local people's economy through collaboration and stakeholder participation.
Keywords: Komodo National Park; Ata Modo; developement; infrastructure; local people